Pelaksanaan Kewajiban Perpajakan Pelaku Usaha Mikro Kecil Menengah Marketplace di Wilayah Kecamatan Duren Sawit - Dwikora Harjo; Aninda Rahmawati; Dani Milleano (Penelitian dan Pengabdian Masyarakat Universitas Bina Insani, 2021)
Regarding the implementation of Government Regulation Number 23 of 2018 concerning tax obligations, there are still MSMEs in the marketplace who do not know their tax obligations. This study was conducted with the aim of analyzing the fulfillment of tax obligations and the obstacles among the MSME marketplace in the Duren Sawit Pratama Tax Service Office, especially in 2020 at the peak of the COVID-19 pandemic. A qualitative approach with descriptive research is the method used in conducting this research. The results show that the fulfillment of tax obligations among the MSME marketplace in the Duren Sawit Pratama Tax Office has not gone well, especially in terms of registration and tax reporting. Some of the obstacles found were the difficulty of identifying and reaching new marketplace MSME taxpayers, so that tax socialization did not run optimally. In addition, knowledge about tax obligations among them is also still very low. As a result, the MSME tax contribution in the marketplace has decreased, with an average tax contribution of only 0.56% during the 2018-2020 period.